2020
DOI: 10.1177/0269881120953993
|View full text |Cite
|
Sign up to set email alerts
|

Paternal exposure to morphine during adolescence potentiates morphine withdrawal in male offspring: Involvement of the lateral paragigantocellularis nucleus

Abstract: Background: Opiate exposure during adolescence perturbs the brain’s maturation process and potentially confers long-term adverse consequences, not only in exposed individuals but also in their posterity. Here, we investigate the outcomes of adolescent paternal morphine exposure on morphine withdrawal profile in male offspring. Methods: Male Wistar rats were chronically subjected to 10 days of an escalating regimen of morphine during adolescence. After a 20-day washout period, adult males were allowed to copula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Also, a previous study presented that the effects of morphine exposure on weight gain pattern were different in male and female Long Evans rats, so that chronic morphine injection inhibited normal weight gain in male rats, whereas in female rats, it improved weight gain (Bobzean, Kokane, Butler, & Perrotti, 2019). On the other hand, it has been reported that weight gain in male offspring whose paternal were chronically exposed to morphine during adolescence was significantly reduced compared to the control group (Azadi, Gompf, & Azizi, 2020). Therefore, morphine intake during adolescence can have long-term effects on the feeding behaviors of the animals (Bodnar, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a previous study presented that the effects of morphine exposure on weight gain pattern were different in male and female Long Evans rats, so that chronic morphine injection inhibited normal weight gain in male rats, whereas in female rats, it improved weight gain (Bobzean, Kokane, Butler, & Perrotti, 2019). On the other hand, it has been reported that weight gain in male offspring whose paternal were chronically exposed to morphine during adolescence was significantly reduced compared to the control group (Azadi, Gompf, & Azizi, 2020). Therefore, morphine intake during adolescence can have long-term effects on the feeding behaviors of the animals (Bodnar, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed surgical protocols are fully described in our previous studies [ 13 , 16 , 27 ]. In brief, adult rats (70 days old) were anesthetized by urethane injection (1.2 g/kg, i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…In the next step, LPGi coordinates were obtained from the rat brain atlas [ 28 ] and right above the nucleus, a tiny hole (2 mm in diameter) was drilled on the skull surface (12 mm caudal to bregma, and 1.5 mm lateral to midline). Spike activities of LPGi neurons were recorded by glass micropipettes (OD: 1.2 mm, ID: 0.94 mm, Sutter Instruments, USA) which were pulled using a horizontal programmable microelectrode puller (P-97, Sutter Instrument, USA) and filled with a solution containing 2% pontamine sky blue dye dissolved in 0.5 M sodium acetate (3–12 MΩ resistance) [ 13 , 16 ]. Micropipettes were gently lowered down into the brain to reach the LPGi region (located nearly 10.2–10.8 mm ventral to the skull level).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azadi and colleagues reported an enhancement in the development of the somatic and affective aspects of naloxone-precipitated morphine withdrawal mediated, at least in part, by alteration of lateral paragigantocellularis nucleus-related circuitry in the male offspring of sires exposed to morphine during adolescence. This study revealed that exposure to morphine in male rats during adolescence increases morphine-induced discharge inhibition in the lateral paragigantocellular nucleus (LPGi) neurons in male offspring [ 81 ]. Additionally, the decay slope of action potentials and the amplitude of after-hyperpolarizations increased in locus coeruleus neurons only in the rat offspring of males exposed to morphine during their adolescence [ 82 ].…”
Section: Opioidsmentioning
confidence: 99%